12 days of in vivo caloric reduction can improve important parameters of aging in humans. (June 2020) - Schöller-Mann, Alica; Matt, Katja; Schniertshauer, Daniel; Hochecker, Barbara; Bergemann, Jörg
Highlights: Yet again, caloric reduction significantly increases DNA repair capacity in humans. Mitochondrial respiratory chain function can benefit from caloric reduction. Higher ATP production rate comes not along with higher ROS levels. mRNA levels of SIRT3 and NDUFS1 were significantly enhanced by caloric reduction. Abstract: Caloric reduction (CR) is considered as the most reasonable intervention to delay aging and age-related diseases. Numerous studies in various model organisms provide the main basis for this hypothesis. Human studies exist, but they differ widely in study design, characteristics of test persons and study outcome. In this study we investigated CR in humans on a molecular level to gain a better understanding in these processes. For that purpose, we analyzed human peripheral blood mononuclear cells of healthy people fasting according to F.X. Mayr. In a previous study our group could show a significantly improved DNA repair capacity after fasting. Here we were able to confirm these findings despite a slightly modified fasting therapy. Furthermore, the function of the mitochondrial respiratory chain and the mRNA levels of the mitochondria-associated genes SIRT3 and NDUFS1 were significantly affected by CR. However, these changes were only detectable in people who exhibited no improvement in DNA repair capacity. In contrast to that we could not observe any changes in ROS levels, mitochondrial DNA copy number and non-mitochondrial respiration. Altogether our results reveal that CR in form of F. X. Mayr therapy is able to positively influence several cellular parameters and especially mitochondrial function.